Development of an Interactive Tourism Website for Simeulue Promotion - Sultanu Makrifat; Ully Muzakir; Nazuarsyah (Jurnal Inotera, 2026)
Tourism is a strategic sector in supporting regional economic growth, making digital media increasingly important for promotion in the information technology era. Simeulue Regency has significant natural and marine tourism potential; however, its digital promotion media is still not fully optimized. This study aims to develop an interactive tourism website to support tourism promotion and improve public access to tourism information. The system was developed using the Agile Scrum method with an iterative sprint approach. The resulting website provides destination information, interactive maps, and dynamic content management features. Black-box testing results indicate that all core functions operate correctly without significant functional errors. Therefore, the system is considered feasible as a digital tourism promotion platform and can be further enhanced in future development.